Development Education in European Rural Areas: The Work Done by NGODs - Martínez-Scott, S.; Monjas-Aguado, R.; Torrego-Egido, L. (Revista Iberoamericana de Estudios de Desarrollo)
Non-governmental organisations for development (NGODs) and civil society organisations (CSOs) are key actors to the development of solidarity, a priority goal in European Union policies. NGODs and CSOs carry out Development Education (DE) projects and programmes, among other tasks. Rural DEAR Agenda-EYD 2015 (Development Education in Rural Areas 2015) is a European project analysing DE initiatives by NGODs and CSOs in rural areas in seven European countries: Italy, Spain, Greece, Poland, Bulgaria, Cyprus, and Malta. A questionnaire was designed and sent to these NGODs/CSOs. In addition, there were three working group sessions in each country, involving all the relevant stakeholders. The project consisted in the analysis of fields of action, target populations, types of funding, action planning, and evaluation. The results show that in rural areas fewer initiatives are conducted, they are not especially designed for their target populations, and they have serious limitations in the aspects analysed.